Addressing Public Health Challenges of Hajj Pilgrims: A Comprehensive Narrative Review - Hermawan Saputra; Arief Tarmansyah Iman; Rustika Rustika; Sheila Rizkia Anjari (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Introduction: The Hajj pilgrimage is a pillar of Islam that must be carried out by every able-bodied Muslim. However, millions of pilgrims who gather each year face complex health challenges, including advanced age, comorbidities, and extreme environmental conditions. This study aims to identify the health risks of hajj pilgrims and the challenges in efforts to improve pilgrim health. Methods: The research method used is a narrative review, collecting related literature from various sources. The results of the study indicate that hajj pilgrim mortality is still high, mainly caused by cardiovascular disease, respiratory disorders, and heat stroke. Results: The mortality rate among Hajj pilgrims ranges from 1-3 per 1,000 per season, with 461 deaths recorded in 2024. Cardiovascular diseases (70%), respiratory infections, and heat stroke are the leading causes. Risk factors include advanced age, diabetes, hypertension, and extreme temperatures. Pilgrims' low compliance with vaccinations, especially meningitis and influenza, increases the risk of disease outbreaks. The crowded environment facilitates respiratory disease transmission, while limited access to healthcare and language barriers further complicate medical response. Health outreach, vaccination programs, international collaboration, and telemedicine are strategic measures that can help reduce mortality rates among Hajj pilgrims by improving health awareness, managing chronic conditions, and ensuring timely medical care. Conclusion: In conclusion, more comprehensive health interventions and are needed to reduce morbidity and mortality among hajj pilgrims.